AB0259 The high basal level antibodies to modified citrullinated vimentin (anti-MCV) – predictive factor of response to tocilizumab therapy in rheumatoid arthritis. (23rd January 2014) - Avdeeva, A.S.; Alexandrova, E.N.; Novikov, A.A.; Panasyuk, E.Y.; Cherkasova, M.V.; Nasonov, E.L.
Abstract : Background: Tocilizumab (TCZ) is a humanized anti-interleukin-6 (IL-6) receptor monoclonal antibody that blocks IL-6 from binding to its receptor. To evaluate the activity of RA, along with DAS 28 is often used clinical disease activity index (CDAI) and simplified disease activity index (SDAI). Given the marked reduction in acute-phase reactants during therapy TCZ, CDAI is the best complex indicator for assessing the effectiveness of therapy than the DAS 28, as it only takes into account the clinical indicators of activity and does not include laboratory data Objectives: To evaluate the frequency of DAS 28, SDAI and CDAI remission during therapy TCZ and identify predictive factors of good response to treatment Methods: Data were obtained from the first Russian open-label, Phase IV, multicenter 24 week study of the efficacy and safety of TCZ in RA. 42 pts with RA (32 woman, mean age 50, 5; 43, 0-55, 0 years, mean disease duration 56, 5; 23, 0-81, 0 months, mean DAS 28 6, 4; 5, 8-7, 05, SDAI 45, 0; 36, 2-57, 0, CDAI 41, 5; 32, 0-53, 0) received 6 intravenous TCZ infusions (8 mg/kg) every 4 weeks, in combination with DMARDs and glucocorticoids. Erythrocyte sedimentation rate – ESR (mm/hr) was determined by Westergren method; serum concentrations of CRP (mg/L) were measured by laser nephelometry; antibodies to modified citrullinated vimentin – anti-MCV (U/ml) were tested using ELISA Results: On the 24-th week of therapy values [Me; interquartile range] DAS 28 were 2.11 (1.29-2.77), SDAI 4, 4 (2, 0-8, 8), CDAI 3, 6 (1, 4-7, 6), the DAS 28 remission (<2, 6) was achieved at 30 patients (71%), SDAI (≤3, 3) - in 13 (31%), CDAI (≤2, 8) - in 14 (33%). Correlation was found with basal level of anti-MCV and DAS 28 (r =0, 4 p=0, 02), SDAI (r =0, 35, p=0.04) and CDAI (r =0, 4 p=0, 02).In depend on the CDAI remission on the 24-th week of treatment, all patients were divided into two groups. RA patients (n=14) who achieved CDAI remission on the 24-th week of therapy TCZ revealed a higher basal level anti-MCV (2236, 1; 979, 7-2492, 8 U/ml) than in the group of patients (n=28) who remained disease activity (502, 9; 49, 6-1107, 7 U/ml p=0, 02). Logistic regression analysis confirmed that patients with a positive determination in serum anti-MCV were more likely to reach CDAI remission at the 24-th week of therapy TCZ than anti-MCV - negative (OR: 18.4; p=0.03). Factors such as gender, age, disease duration, level CRP and ESR had no affect the incidence of remission Conclusions: The high basal level anti-MCV in RA can be consider as a predictive factor of CDAI remission at the 24-th week of therapy TCZ Disclosure of Interest: None Declared